Wavelet Analysis: A Links Between the North Atlantic Oscillation andWinter Drought in the MediterraneanWatersheds of theWestern Rif (North Morocco) - El-Khantoury, Ismail; Obda, Khalid; Achiban, Hassan (European Scientific Journal, ESJ, 2020)
Morocco in general and the Mediterranean watersheds of the Western Rif in particular, occasionally have been affected by the negative impacts of drought, as demonstrated by the drought of 1944-1945, 1980-1984, 1994-95, 1998-2000, 2004-2005, 2011-12 and 2015-2016. This study aims (1) to identify and characterize the dry winters (DJFM) recorded in the Mediterranean watersheds of theWestern Rif, and (2) to analyse the variability of precipitation in this region over the last few decades in relation to the North Atlantic Oscillation (NAO). The results of this study show that the years 1980- 81, 1994-95, 1999-2000 and 2011-12 recorded the most severe winter drought. In addition, the wavelet coherence values between the NAO index and the SPI winter index (DJFM) for the period (1978-79/2014-15) show a very close relationship between the two variables for all time scales (ranging from 2 to 13 years), especially since the early 1990s. The phase angle shows a negative correlation between the drought index (SPI) and the NAO index.